URGENSI PEMBEBASAN PEMBERIAN PATEN VAKSIN COVID-19 DITINJAU DARI PERSPEKTIF HUKUM NASIONAL - Yogaputri, Made Ayu Okshana; Dahana, Cokorda Dalem (Kertha Negara : Journal Ilmu Hukum, 2023)
The goal of this study is to evaluate the legal certainty and risk associated with a Covid-19 vaccine invention's patent uncertainty in the pharmaceutical industry, particularly in times of emergency. This study employs statutory and factual approaches along with normative legal research techniques . The results of the study show that the legal certainty of obtaining a patent for an invention and the legal risks that will arise have been regulated explicitly and implied in Law Number 13 of 2016 concerning Patents, Government Regulation Number 77 of 2020 concerning Procedures for Granting Patent Compulsory Licensing, and Presidential Decree Number 11 of 2020 Concerning the Establishment of a Public Health Emergency for CoronaVirus Disease 2019. From a legal perspective, patent reactions can pose a risk which is considered based on the legal basis in the regulation of the Patent Law.